The Influence of Sexuality Education on Five-Year-Old Children’s Understanding of Safe and Unsafe Touch - Eltira Frasiska; Wulansari Vitaloka (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Early childhood is a critical period for establishing foundational awareness of body boundaries and personal safety. Developmentally appropriate sexuality education plays an essential role in supporting children’s understanding of safe and unsafe touch as part of early prevention efforts against abuse. This study aims to analyze the influence of sexuality education on five-year-old children’s understanding of safe and unsafe touch concepts. A descriptive qualitative approach was employed to explore children’s experiences, responses, and interpretations during learning activities. Data were collected through participant observation, in-depth interviews with teachers and parents, and documentation of classroom activities and children’s work. The findings indicate that sexuality education enhances children’s awareness of body ownership, enables them to distinguish between safe and unsafe touch, and promotes basic self-protection behaviors such as refusing inappropriate contact and reporting to trusted adults. The study concludes that developmentally appropriate sexuality education contributes significantly to strengthening early self-protection capacities. It is recommended that educators and parents collaboratively implement structured, age-appropriate sexuality education programs to reinforce children’s safety awareness in everyday contexts.